Juan de Arellano (1614–1676) and His Flower Garlands - Alice Joan Hu (Ибероамериканские тетради)
The work of Juan de Arellano, a prominent Spanish painter and creator of flower garland paintings, proved influential in the 17th century Spanish art. Arellano’s creative path was far from easy. In the early stage of Juan de Arellano’s career, he concentrated on religious themes and human figures, but neither reflected his particular talent. Inspired by Flemish (Daniel Seghers) and Italian artists (Mario Nuzzi), Arellano started to paint flower still lifes, such as flowers in a vase, flowers in a basket and images framed by a flower garland. Paintings with flower garlands gained popularity not only in Flemish art, but also in Spain in the 17th century. Nowadays flower garland paintings are still popular with viewers and researchers, hence the number of garland paintings exhibitions, for instance, «Ars vivendi. Frans Snyders and 17th century Flemish Still Lifes» in the Hermitage (2024). Arellano transitioned from religious compositions with garlands through landscapes with garlands to floral still lifes. Thus, the trend towards decorativism manifested itself as decorative art flourished in Spain in the second half of the 17th century.